SAT0074 Persistence with metformin treatment and onset of rheumatoid arthritis. (15th June 2017) - Naffaa, ME; Rosenberg, V; Chodick, G; Shalev, V; Tiosano, S; Amital, H
Abstract : Background: Several studies have suggested that metformin, an oral hypoglycemic agent, possess an anti-inflammatory property and may have a role in the treatment of rheumatoid arthritis (RA) 1, 2, but little is known on its preventive effects. Objectives: To examine the association between persistence with metformin and the onset of RA. Methods: Using the computerized medical database of a large health organization in Israel (Maccabi Healthcare Services, MHS) we have identified incident RA cases among new users of metformin between 1998 and 2014. Included were patients aged 18 or above with one year of follow up before and after the therapy initiation. RA was defined according to physician diagnoses. Participants were followed until the earliest of the following dates: onset of RA, leaving MHS, death, end of follow up (1.1.2016). Persistence with metformin was assessed by calculating the mean proportion of follow-up days covered (PDC) with metformin during the study period. Results: A total of 113, 749 eligible patients were included. During the study follow up period (794, 386 person-years) we identified 600 incident cases (incidence rate of 75 cases per 100, 000 PY). The incidence of RA in women (111 per 100, 000 PY) was higher compared to men (42 per 100, 000 PY). In a multivariable model, persistence with metformin (PDC≥80%) was associated with lower risk of RA (hazard ratio (HR) 0.66; 95% confidence interval (CI) 0.53–0.82) compared to non-persistent participants (PDC<20%). Figure 1 shows the hazard function according to persistence with metformin treatment. Similar risk reduction was observed among men but did not reach statistical significance (HR=0.85; 95% CI 0.54–1.32). Conclusions: In the present study, we observed an association between high persistence to metformin therapy and reduced risk of developing RA in women. Disclosure of Interest: None declared